Allergic Contact Dermatitis Is Associated with Significant Oxidative Stress - S. Kaur; K. Zilmer; V. Leping; M. Zilmer (Hindawi Limited, 2014)
Background. Research has confirmed the involvement of oxidative stress (OxS) in allergic contact dermatitis whilst other inflammation-related biomarkers have been less studied. Objective. To evaluate systemic levels of selected inflammatory markers, OxS indices and adipokines as well as their associations in allergic contact dermatitis. Methods. In 40 patients, interleukin- (IL-) 6, monocyte chemoattractant protein (MCP-1), and IL-10 levels were measured in sera with the Evidence Investigator Cytokine & Growth factors High-Sensitivity Array, total peroxide concentration (TPX) and total antioxidant capacity (TAC) by means of spectrophotometry, and the plasma concentrations of adiponectin and leptin by the quantitative sandwich enzyme immunoassay technique. Results. TNF-α level (P < 0.01) and TPX (P < 0.0001) were increased whilst IL-10 (P < 0.05) and TAC (P < 0.0001) were decreased in the patients as compared to controls. Correlation and multiple linear regression analysis identified both, TPX and TAC (inversely), as possible independent markers for evaluating allergic contact dermatitis. Adiponectin level in patients was increased (P < 0.0001), but neither adiponectin nor leptin correlated significantly with the biomarkers of inflammation or OxS. Conclusion. OxS parameters, especially TPX and OSI, reflect the degree of systemic inflammation associated with allergic contact dermatitis in the best way. The relation between OxS and adiponectin level warrants further studies.